KRIMINALITAS DAN PERANAN HUKUM - Mufid, Mufid (Jurnal Bestari, 1992)
Michael Franzese was famous as one of Mafia's "bosses". Once, he shocked his gang to convert. He would release gunsekf from the last history to face the other days in paradise. Ot was interesting enough to trace the background of his convertion. Suddenly, he fell in love when he found the true love from Cammy Garcia. Is it a kind of phenomena that naturally eveyone tends to do the best for himself and others? Thomas Hobbes rejected that statement although he could not release himself from life long dialectical monologue. When he stated homo homini lupus, he then was doubtfull to th nature of man before the death. Fear of death led mankind to be usefull for others. The role of law, however, guide everyman to create the mondial paradise. It can be regarded as the fundamental basci of historical equilibrium.